The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jcp.22981
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields (EMFs) and adenosine receptors modulate prostaglandin E2 and cytokine release in human osteoarthritic synovial fibroblasts

Abstract: Synovial fibroblasts (SFs) contribute to the development of osteoarthritis (OA) by the secretion of a wide range of pro-inflammatory mediators, including cytokines and lipid mediators of inflammation. Previous studies suggest that electromagnetic fields (EMFs) may represent a potential therapeutic approach to limit cartilage degradation and control inflammation associated to OA, and that they may act through the adenosine pathway. Therefore, we investigated whether EMFs might modulate inflammatory activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 59 publications
4
86
1
Order By: Relevance
“…Moreover, PEMFs are able to mediate the upregulation of A 3 ARs in bovine chondrocytes and synoviocytes (Varani et al, 2008;De Mattei et al, 2009). These data have been further confirmed in human synoviocytes where the copresence of A 3 ARs and PEMFs reduces the release of PGE2, IL-6, and IL-8, whereas it increases IL-10 release (Ongaro et al, 2012). Recently, in human T/C-28a2 chondrocytes and human FOB 1.19 osteoblasts, PEMFs and A 3 AR stimulation have been seen to reduce PGE2, IL-6, and IL-8 production, suggesting their potential in the treatment of inflammatory bone and joint disorders .…”
Section: E Rheumatoid Arthritis and Ostheoarthritismentioning
confidence: 53%
“…Moreover, PEMFs are able to mediate the upregulation of A 3 ARs in bovine chondrocytes and synoviocytes (Varani et al, 2008;De Mattei et al, 2009). These data have been further confirmed in human synoviocytes where the copresence of A 3 ARs and PEMFs reduces the release of PGE2, IL-6, and IL-8, whereas it increases IL-10 release (Ongaro et al, 2012). Recently, in human T/C-28a2 chondrocytes and human FOB 1.19 osteoblasts, PEMFs and A 3 AR stimulation have been seen to reduce PGE2, IL-6, and IL-8 production, suggesting their potential in the treatment of inflammatory bone and joint disorders .…”
Section: E Rheumatoid Arthritis and Ostheoarthritismentioning
confidence: 53%
“…The algogenic effect of electromagnetic fields has also been observed with pulsed MFs in osteoarthritic disease [45][46]. Musaev and colleagues reported that lowfrequency pulsed MFs have analgesic, vasoactive, neuronstimulating, and trophic effects in patients with diabetic polyneuropathy, which has a similar sensory profile as FM [26].…”
Section: Discussionmentioning
confidence: 92%
“…Electromagnetic field stimulation led to up-regulation of A 2A receptors in synovial fibroblasts and it was suggested that adenosine, acting through both A 1 and A 2A receptors, had anti-inflammatory activity to control joint inflammation [443]. A 2A and A 3 receptor agonists have been shown to modulate PGE 2 and cytokine release in human osteoarthritic fibroblasts [444]. Adenosine receptors also regulate inflammatory responses in human synoviocytes [445].…”
Section: Osteoarthritismentioning
confidence: 99%